吹扫捕集-气相色谱法测定海水中的氟氯烃 - 蔡明刚; 黄鹏; 张麋鸣; 李文权 (2013)
氟氯烃(CHlOrOfluOrOCArbOnS,CfCS)是一类重要的温室气体,可作为示踪剂应用于海洋学中。本研究建立了一套吹扫捕集系统以分析海水中CfCS。对吹扫捕集系统测定条件进行了考察,优化的实验条件为:捕集温度#60℃,吹扫时间8 MIn,吹扫气流速20 Ml/MIn,脱附时间1.5 MIn,脱附温度130℃。本方法简单、灵敏,CfC-11,CfC-12,CfC-113及CCl4(CArbOn TETrACHlOrIdE)的检出限分别为0.004,0.008,0.001及0.006PMOl/l,回收率分别为99.92%±1.77%,98.77%±1.50%,98.95%±3.92%及97.13%±1.78%,标准工作曲线的线性相关系数均大于0.99。本方法成功应用于27次南极科学考察期间采集的普里兹湾水样的测定。 A purge and trap system was developed for the determination of chlorofluorocarbons(CFCs) in seawater.The optimum conditions were as follows: trap temperature of -60 ℃,purge time of 8 min,purge flow rate of 20 mL/min,desorption time of 1.5 min,desorption temperature of about 130 ℃.The method is simple and sensitive,the detection limit of CFC-11,CFC-12,CFC-113 and CCl4 were 0.004,0.008,0.001 and 0.006 pmol/L,and the recoveries of them were 99.92%±1.77%,98.77%±1.50%,98.95%±3.92% and 97.13%±1.78%,respectively.The R2 values of all the calibration curves were greater than 0.99.This method was successfully used in the analysis of the samples collected in Prydz Bay in 27th Chinese Antarcitc Research Expedition. 国家自然科学基金(No.41076133)资助项目